Co@NH2-MIL-125(Ti): cobaloxime-derived metal–organic framework-based composite for light-driven H2 production. Issue 1 (26th November 2014) - Nasalevich, M. A.; Becker, R.; Ramos-Fernandez, E. V.; Castellanos, S.; Veber, S. L.; Fedin, M. V.; Kapteijn, F.; Reek, J. N. H.; van der Vlugt, J. I.; Gascon, J.
Abstract : Encapsulation of cobalt catalyst within the pores of a photoresponsive MOF results in very efficient and fully recyclable noble metal-free photocatalyst for hydrogen evolution from water under visible light illumination. Abstract : We present a synthetic strategy for the efficient encapsulation of a derivative of a well-defined cobaloxime proton reduction catalyst within a photoresponsive metal–organic framework (NH2 -MIL-125(Ti) ). The resulting hybrid systemCo@MOF is demonstrated to be a robust heterogeneous composite material. Furthermore, Co@MOF is an efficient and fully recyclable noble metal-free catalyst system for light-driven hydrogen evolution from water under visible light illumination.